Đặc điểm chất lượng Ruby, Saphir từ các kiểu mỏ chính ở Việt Nam - Khôi, Nguyễn Ngọc; Nhung, Ngụy Tuyết; Thuyết, Nguyễn Thị Minh (Vietnam Journal of Earth Sciences, 2012)
SUMMARYQuality characteristics of rubies and sapphires from main deposit types of VietnamFor the last decades Vietnam has been considered as a country with great potential for ruby and sapphire gemstones. Deposits and ocurrences of most corundum deposit types have been discovered in different regions of our country, of which of most interest are: marble-hosted deposit type with Luc Yen and Quy Chau deposits as representatives; metapelite-hosted deposit type with typical deposits as Tan Huong and Truc Lau and basalt-related deposit type with typicalrepresentative as Dak Ton deposit.Being formed in different tectonic settings and geological environments, these deposit types possess their own attributes in mineralogy,150 morphology, texture, hosting lithology as well as economic value.Different geological environments also determined the difference in gem-quality characteristics of rubies and sapphires, which arereflected in their morphology, color and clarity.According to these criteria, the quality of corundums from 3 main deposit types of Vietnam changes as follows:- Corundums in matrix from the metapelite hosted deposit type are usually of dark gray to gray blue color, and very low transparency due to high percentage of opaque mineral inclusions as magnetite, ilmenite... and due to high fracturing.Most of them are not of gem quality. Nevertheless, corundums from placers in Tan Huong and Truc Lau deposits have better coloration and clarity.- Corundums from both hosting rocks and placers of the marble hosted deposit type (Luc Yen and Quy Chau deposits) are characterized by dominant red hue with various hints, with the saturation varyingfrom dull to very vivid, and tone changing from light to very dark. Inclusions are very diversified, but their contents are not high, that is why the transparency of corundums is good. Corundums from this deposit type is of highest quality, some of them are comparable with Mogok stones which are considered as the best in the world.- Corundums from the basalt related deposit type are usually of dark blue, green blue, yellow color, some belong to BGY type. The saturationchanges from dull to slightly vivid, the tone from light to dark. Inclusions are plentiful, but their content is low. Corundums from this deposit type are of medium gem quality.As a conclusion, corundums from the marble hosted deposit type are of the highest quality, corundums from the basalt related deposit type ofintermediate quality, and corundums from the metapelite hosted deposit type are of the lowest quality.